Near infrared calibrations for rapid screening of foliar nitrogen and phosphorus in Eucalyptus pellita F. muell - Alwi, Agustan (2022)
Eucalyptus pellita F. Muell. has become an important tree species in the forest plantations of South-East Asia, and in Malaysian Borneo in particular, to replace thousands of hectares of Acacia mangium Willd., which has suffered significant loss caused by Ceratocystis manginecans infection in Sabah, Malaysia. Nitrogen (N) and phosphorus (P) fertilization at the time of planting are essential to optimize E. pellita establishment and growth in forest plantations. Traditionally, plant nutrient content is analyzed via wet chemistry methods using ground, dried foliar samples with the associated cost of analysis of many leaf samples. Generally, this chemical technique requires large amount of chemicals and reagents, which may be unfriendly to environment and hazardous to health. This study aims to quantitatively estimate N and P elements in E. pellita foliage samples by means of near- infrared (NIR) reflectance spectroscopy. This method is non- destructive, rapid and cost-effective. In order to be used effectively, the NIR spectra must be calibrated with foliar samples that have also been analyzed using reference methods. In this present study, the nutritional status of the foliage was investigated with the aim to develop near- infrared spectroscopic calibrations that can be used to monitor and quantify nutrient status, particularly total foliar nitrogen (N) and phosphorus (P) in the field. The spectrum data was captured using VIAVI 1700 hand-held spectrometer. Spectra acquired on fresh foliage in situ on the tree could be used to predict N and P with accuracy suitable for operational decision- making with regards to fertilizer application. Accuracy of spectra acquired on dried ground foliage could be used to predict N and P within a relative error of 10% (R2 c, r2 CV, RMSEP, RPD of = 0.77, 0.71, 0.02 g. 100 g-1, 1.9 for foliar P and = 0.90, 0.88, 0.21 g. 100 g-1, 3.0 for foliar N on dried ground foliage). Therefore, the ultimate application of this near-infrared spectroscopic calibration is in situ nutrient monitoring, particularly in longitudinal studies in fertilizer trial plots and forest operations, as the non-destructive nature of NIR spectroscopy would enable regular monitoring of individual leaves over time without the need to destructively sample them. This would aid the temporal and spatial analysis of field data.